Relationship between consumer confidence and stock market index in Vietnam: Research impacts of the passion of Covid-19 - Lu, Xuan Trang; Phan, Thi Hang Nga (Journal of Finance - Marketing Research, 2023)
The article, studies the relationship between consumer confidence and the stock market index in Vietnam's stock market in the context of the Covid-19 pandemic shock, data collected from 2012Q1 to 2021Q4 from Nielsen data sources. Consumer confidence is measured by the consumer confidence index (CCI), and the stock market index (SMI). Covid 19 impact context using dummy variables. The authors use the PVAR model to solve the set goals. Research results show that there is a strong positive relationship between consumer confidence and the stock market index in Vietnam in the period from 2012 to 2021. In addition, shocks of the past CCI and SMI value also affect current CCI and SMI values. This shows that when consumer confidence is in a positive direction, the SMI will also be in a positive direction and vice versa. In addition, the results showed that Covid 19 did not significantly affect the above relationship. From the research results, the authors propose governance implications to attract more investors to participate in the stock market, contributing to promoting capital in the circulating economy more effectively.